Optimal operation of active distribution network considering energy storage-equipped soft open points - Samarendra Pratap Singh; Neeraj Kanwar; Amit Saraswat (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2025)
The Soft Open Point (SOP) is a cutting-edge electronic apparatus consisting of voltage source converters linked by a DC capacitor, designed to connect neighbouring distribution feeders. The primary roles of SOPs include managing active power flow and offering reactive power assistance. By incorporating energy storage, this device gains the ability to regulate active power flow over time. This study proposes a framework that takes into account the capabilities of an energy storage-equipped SOP (ESOP) across temporal and spatial dimensions, along with demand side management (DSM) and coordinated dispatch of active and reactive power from solar PV and wind turbine generators. The aim is to optimise the operational costs of an active distribution network (ADN). To accurately depict demand, a voltage-sensitive exponential load model is employed. The suggested framework is formulated as a mixed integer nonlinear programming (MINLP) model, implemented on a modified IEEE 33 bus distribution network, and solved using the DICOPT solver in GAMS.